The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0366-69132004000400009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of industrial wastes in mortar layers deposited on stainless steel sheets of sinks

Abstract: Metal sinks are broadly produced with stainless steel sheets. These steel sheets are thin and may easily bend under mechanical forces. Wood or a mortar layer is used to strengthen the steel sink. In the last decade mortars have been used to replace wood. The mortar mixture is poured on the backside of the metal sink. After setting and hardening, the mortar prevents the sink metal sheet from bending.Since the concern with the cost of raw materials and with the environment, some industries are trying to use indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
1
4
0
4
Order By: Relevance
“…The results of this study revealed that both these events adversely alter the compressive strength of MTA. In addition, in the blood‐contaminated groups, an absence of acicular crystals, characteristic of hydrated calcium sulphoaluminate (ettringite) (Gemelli et al. 2004, Stutzman 2004), that have a potential role in forming inter‐crystal bonds (Ismail et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study revealed that both these events adversely alter the compressive strength of MTA. In addition, in the blood‐contaminated groups, an absence of acicular crystals, characteristic of hydrated calcium sulphoaluminate (ettringite) (Gemelli et al. 2004, Stutzman 2004), that have a potential role in forming inter‐crystal bonds (Ismail et al.…”
Section: Discussionmentioning
confidence: 99%
“…In both control groups, a wide variety of distinctive crystalline formations around cross-sections of micro-channels were seen (Figs 4 and 5i). Such formations included angular and laminar crystals along with two main forms of acicular crystals characteristic of hydrated calcium sulphoaluminate (ettringite) (Gemelli et al 2004). These characteristic formations include jagged or spiky ball-like clusters and bundles of longer spanning structures that interlink other crystals (Fig.…”
Section: Semmentioning
confidence: 99%
“…Nesse sentido, vários pesquisadores [15][16][17][18][19] têm se dedicado à busca de alternativas para baratear os materiais de construção, dentre essas, temse o uso de resíduos minerais e da construção. Seguindo essa abordagem, observou-se [20] que dependendo da composição química e distribuição do tamanho de partículas, vários resíduos industriais podem ser usados em argamassas para a construção civil, seja em substituição parcial ao cimento ou ao agregado miúdo. Diversos estudos [8,[20][21][22][23][24] vêm apresentando sucessos na utilização de resíduos inorgânicos para a produção de argamassas, evidenciando sua adequabilidade como matérias-primas alternativas para a construção civil.…”
Section: R R Menezes J Farias Filho H S Ferreira G a Nevesunclassified
“…É um material pulvurulento, constituído de silicatos e aluminatos de cálcio com inúmeras propriedades e características, que ao serem misturados com água, hidratam-se, sendo capazes de desenvolver elevada resistência mecânica ao longo do tempo. Foi observado que dependendo da composição química e distribuição do tamanho de partículas, vários resíduos industriais podem ser usados em argamassas para a construção civil, seja em substituição parcial ao cimento ou ao agregado miúdo [3]. Diversos estudos vêm apresentando sucessos na utilização de resíduos inorgânicos para a produção de argamassas, evidenciando sua adequabilidade como matérias-primas alternativas para a construção civil.…”
Section: Introductionunclassified